Sustainable management of pastoral resources in Mauritania - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Participatory approaches are applied in research to define the parties involved and their respective roles in the implementation of the Pastoral Code in the communities of Moït and Bokoul in the Monguel area (Gorgol region). The research also determines the relationship between the Code and decentralization, and potential areas of conflict and bottlenecks that may emerge when the Code is applied.